Book Review: A Handbook on Supply Chain Management - Habib, Dr. Md. Mamun; Pathik, Bishwajit Banik (International Journal of Supply Chain Management, 2013)
Supply Chain Managementcan be viewed as both an emergent field of practice and an emerging academicdiscipline. For academicians, it is an emerging field of study, where theprimary outputs are theory, insights, and research. For practitioners, it is anemergent field where the outputs involve new relationships, new developments,and new practice. Supply chain management is ultimately about influencing thebehavior of professionals and enriching knowledge of students in particulardirections and in particular ways. Supply chain management, a field developedfrom business practice and research, is undergoing a major transportation. Itis changing from tactical in nature (where the major focus is on cost anddelivery) to a field that is strategic in nature. This book is a compilation of18 papers that primarily take stock of developments in theory and practice insome important areas of current research.